Retrospective analysis of sorafenib combined with interferon α-1b, interleukin-2, and thalidomide as maintenance therapy in FLT3-ITD-positive acute myeloid leukemia - Cheng, Cheng; Mi, Ruihua; Li, Dongbei; Chen, Lin; Wei, Xudong (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the clinical efficacy of maintenance therapy with sorafenib combined with interferon α-1b, interleukin-2, and thalidomide (the ITI regimen) in patients with FLT3-ITD-positive acute myeloid leukemia (AML).Methods19 FLT3-ITD(+) AML patients were retrospectively analyzed, who received the sorafenib combined with ITI regimen as maintenance therapy after achieving remission at Affiliated Cancer Hospital of Zhengzhou University (January 2014–December 2024). Minimal residual disease (MRD) levels were monitored, and clinical outcomes, including survival duration, were assessed.ResultsThis study included 19 patients (9 males, 10 females) with a median age at diagnosis of 59 years (range: 21–76). The median white blood cell count was 32.25×109/L (range: 0.7–254×109/L). Among them, 13 patients (68.4%) maintained sustained MRD negativity during sorafenib combined with TI regimen therapy, while 3 patients experienced morphological relapse and 3 had molecular relapse. Median overall survival (mOS) was not reached, with 12- and 24-month OS rates of 100% (19/19) and 94.7% (18/19), respectively. During maintenance therapy with sorafenib combined with ITI, median relapse-free survival (mRFS) was also not reached, with 12- and 24-month RFS rates of 73.7% (14/19) and 57.9% (11/19), respectively.ConclusionThe sorafenib combined with ITI regimen is an effective maintenance therapy for FLT3-ITD (+) AML, significantly reducing relapse risk and prolonging survival.